Detection of Micrometer-Sized Virus Aerosols by Using a Real-Time Bioaerosol Monitoring System - Seo, Hyunsoo; Jeong, Young-Su; Bae, Jaekyung; Choi, Kibong; Seo, Moon-Hyeong (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study investigates a real-time handheld bioaerosol monitoring system for the detection of biological particles using UV-LED and light-induced fluorescence technology. Biological particles produce both scattering and fluorescence signals simultaneously, which can help distinguish them from general particles. The detected scattering, fluorescence, and simultaneous signals are then converted into photon signals and categorized based on predetermined criteria. A reliable biological particle generator was required to validate the performance of the system. This study explores the use of an M13 bacteriophage as a virus simulant of biological agents and employs a customized inkjet aerosol generator to produce M13 bacteriophage aerosols of a specific size by controlling the concentration of M13. We confirmed that micro-sized, narrowly dispersed M13 aerosols were efficiently generated. Additionally, we confirmed the performance of this real-time handheld bioaerosol monitoring system by detecting viruses.